3D Artificial Solid‐Electrolyte Interphase for Lithium Metal Anodes Enabled by Insulator–Metal–Insulator Layered Heterostructures. Issue 13 (25th February 2021) - Zhai, Pengbo; Wang, Tianshuai; Jiang, Huaning; Wan, Jiayu; Wei, Yi; Wang, Lei; Liu, Wei; Chen, Qian; Yang, Weiwei; Cui, Yi; Gong, Yongji
Abstract: Despite considerable efforts to prevent lithium (Li) dendrite growth, stable cycling of Li metal anodes with various structures remains extremely difficult due to the direct contact of the liquid electrolyte with Li. Rational design of solid‐electrolyte interphase (SEI) for 3D electrodes is a promising but still challenging strategy for preventing Li dendrite growth and avoiding lithium–electrolyte side reactions in Li‐metal batteries. Here, a 3D architecture is constructed with g‐C3 N4 /graphene/g‐C3 N4 insulator–metal–insulator sandwiched nanosheets to guide uniform Li plating/stripping in the van der Waals gap between the graphene and the g‐C3 N4, and the function of which can be regarded as a 3D artificial SEI. Li deposition on the surface of g‐C3 N4 is suppressed due to its insulating nature. However, its uniform lithiophilic sites and nanopore channels enable homogeneous lithium plating between the graphene and the g‐C3 N4, prohibiting the direct contact of the electrolyte with the Li metal. The use of the g‐C3 N4 ‐layer‐modified 3D anode enables long‐term Li deposition with a high Coulombic efficiency and stable cycling of full cells under high cathode loading, limited Li excess, and lean electrolyte conditions. The concept of a 3D artificial SEI will shed light on developing safe and stable Li‐metal anodes. Abstract : A 3D artificial solid‐electrolyte interphase (SEI) based on a g‐C3 N4 layer, which possesses high structural and compositional homogeneity, is proposed to guide conformal Li deposition in the van der Waals gap between graphene and the g‐C3 N4 . The design of a 3D artificial SEI enables stable cycling of Li metal anodes and provides potential for achieving high‐energy‐density Li metal batteries.